Kompetensi yang harus dimiliki seorang pustakawan (pengelola perpustakaan) - Muhammad Riandy Arsin Siregar (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2015)
Competency is defined as a benchmark to determine the extent of the ability of librarians in    using the knowledge they can get and skills.Librarian is a person who performs activities of libraries by providing services to the public in accordance with the duties of their parent institutions based on library science. Librarians must meet the standards of competence or the ability in the field. So from the competency standards set by the professional organizations of librarians performance benchmarks can be set.